2017
DOI: 10.1111/dom.13088
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic inertia in the treatment of hyperglycaemia in patients with type 2 diabetes: A systematic review

Abstract: AimsTherapeutic inertia, defined as the failure to initiate or intensify therapy in a timely manner according to evidence‐based clinical guidelines, is a key reason for uncontrolled hyperglycaemia in patients with type 2 diabetes. The aims of this systematic review were to identify how therapeutic inertia in the management of hyperglycaemia was measured and to assess its extent over the past decade.Materials and MethodsSystematic searches for articles published from January 1, 2004 to August 1, 2016 were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
269
0
19

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 297 publications
(306 citation statements)
references
References 77 publications
(346 reference statements)
18
269
0
19
Order By: Relevance
“…As with lower‐middle and upper‐middle‐income countries, this finding may reflect delays in treatment intensification but for different reasons. A possible contributing factor is conservative management of patients by clinicians, as has been documented previously . In addition, the current stepwise approach to treatment intensification that is advocated by major treatment guidelines may lead to prolonged periods of hyperglycaemia in between steps .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As with lower‐middle and upper‐middle‐income countries, this finding may reflect delays in treatment intensification but for different reasons. A possible contributing factor is conservative management of patients by clinicians, as has been documented previously . In addition, the current stepwise approach to treatment intensification that is advocated by major treatment guidelines may lead to prolonged periods of hyperglycaemia in between steps .…”
Section: Discussionmentioning
confidence: 98%
“…Treatment intensification is recommended when patients remain above their HbA1c targets for >3 months after the last intervention. Despite these recommendations, available data, mainly from Europe and North America, indicate poor attainment of glycaemic targets and infrequent implementation of timely treatment intensification . Moreover, real‐world data on the management of T2D are scarce in many low‐ and middle‐income countries, in which the rising disease prevalence is a concern.…”
Section: Introductionmentioning
confidence: 99%
“…Significant covariates were HbA1c concentrations at baseline, duration with diabetes and attainment of higher education. The increase in antidiabetic medication prescribed to the SMBG cohort over the course of the present study illustrates the potential of obtaining and using BG profiles to facilitate a more targeted approach to prescribing and to overcome the issue of clinical inertia in the treatment of hyperglycaemia in Type 2 diabetes [31]. HR, hazard ratio; SMBG, self-monitoring of blood glucose.…”
Section: Discussionmentioning
confidence: 76%
“…This is a common, long‐recognized factor limiting HbA1c goal attainment in many patients with T2D, attributed to multiple clinician‐related factors including lack of treatment target awareness and concerns regarding patient adherence and potential for medication side effects . Multiple studies, including those in patients on metformin monotherapy, have demonstrated median delays in excess of 1 year to appropriate treatment intensification for patients with T2D not at HbA1c goal . Given its multifactorial nature, clinical inertia is a challenging issue to address; however, safe, effective and convenient treatment‐intensification strategies should be enabling in this regard.…”
Section: Discussionmentioning
confidence: 99%